Evaluation of the Phytochemical, Antioxidant, Enzyme Inhibition, and Wound Healing Potential of Calotropis gigantea (L.) Dryand: A Source of a Bioactive Medicinal Product - Alafnan, Ahmed; Sridharagatta, Swathi; Saleem, Hammad; Khurshid, Umair; Alamri, Abdulwahab; Ansari, Shabana Yasmeen; Zainal Abidin, Syafiq Asnawi; Ansari, Siddique Akber; Alamri, Abdulhakeem S.; Ahemad, Nafees; Anwar, Sirajudheen (Frontiers in Pharmacology, 2021)
Traditionally, plants of the genus Calotropis have been used to cure various common diseases. The present research work explores the chemical and biological characterization of one of the most common species of this genus, i.e., Calotropis gigantea (L.) Dryand (syn. Calotropis gigantea (L.) Dryand.), having multiple folklore applications. The ethanolic extract of leaves of Calotropis gigantea (L.) Dryand was analyzed for the phytochemical composition by determining the total bioactive (total phenolic and total flavonoid) contents and UHPLC-MS secondary metabolites analysis. For phytopharmacological evaluation, in vitro antioxidant (including DPPH, ABTS, FRAP, CUPRAC, phosphomolybdenum, and metal chelation antioxidant assays) activities, enzyme inhibition potential (against AChE, BChE, α-amylase, and tyrosinase enzymes), and in vivo wound healing potential were determined. The tested extract has been shown to contain considerable flavonoid (46.75 mg RE/g extract) and phenolic (33.71 mg GAE/g extract) contents. The plant extract presented considerable antioxidant potential, being the most active for CUPRAC assays. Secondary metabolite UHPLC-MS characterization, in both the positive and negative ionization modes, indicated the tentative presence of 17 different phytocompounds, mostly derivatives of sesquiterpene, alkaloids, and flavonoids. Similarly, the tested extract exhibited considerable inhibitory effects on tyrosinase (81.72 mg KAE/g extract), whereas it showed weak inhibition ability against other tested enzymes. Moreover, in the case of in vivo wound healing assays, significant improvement in wound healing was observed in both the tested models at the doses of 0.5 percent w/w (p < 0.001) and 2.0 percent w/w (p < 0.01) on the 16th day. The outcomes of the present research work suggested that C. gigantea (L.) Dryand plant extract could be appraised as a potential origin of bioactive molecules having multifunctional medicinal uses.